2007
DOI: 10.1016/j.jss.2007.02.046
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxicity of Pseudomonas Secreted Exotoxins Requires OxyR Expression

Abstract: Taken together, our data indicate that OxyR regulates the secretion of potent cytotoxic factors by P. aeruginosa.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 38 publications
1
12
0
Order By: Relevance
“…Previous results from our group already established a similar link between oxidative stress and inhibition of siderophore-mediated iron uptake in pseudomonads, because the inactivation of the cytochrome c biogenesis gene ccmC resulted in increased oxidative stress and impaired utilization of ferrisiderophores (Baysse et al, 2003;Baert et al, 2008). Our results partially explain why a P. aeruginosa oxyR mutant shows a decreased virulence in animal models (Lau et al, 2005;Melstrom et al, 2007). (1), oxyR mutant (2), complemented oxyR with pBBR-oxyR (3), wild type with pBBR-oxyR (4) and wild type with a pBBR empty vector (5) in CAA1EDDHA (left panel) or in CAA150 mM FeCl 3 (right panel).…”
Section: Discussionsupporting
confidence: 82%
“…Previous results from our group already established a similar link between oxidative stress and inhibition of siderophore-mediated iron uptake in pseudomonads, because the inactivation of the cytochrome c biogenesis gene ccmC resulted in increased oxidative stress and impaired utilization of ferrisiderophores (Baysse et al, 2003;Baert et al, 2008). Our results partially explain why a P. aeruginosa oxyR mutant shows a decreased virulence in animal models (Lau et al, 2005;Melstrom et al, 2007). (1), oxyR mutant (2), complemented oxyR with pBBR-oxyR (3), wild type with pBBR-oxyR (4) and wild type with a pBBR empty vector (5) in CAA1EDDHA (left panel) or in CAA150 mM FeCl 3 (right panel).…”
Section: Discussionsupporting
confidence: 82%
“…There is a growing realization of the role of peroxide-sensing regulators in adapting to this environmental shift through the control of processes such as virulence factor expression (74,90) and biofilm formation (99,119). Furthermore, the lethality of some antibiotics is due, at least in part, to increased production of ROS (58), and it has been demonstrated that the levels of oxidative stress protective enzymes can affect antibiotic resistance levels (6).…”
Section: Resultsmentioning
confidence: 99%
“…In the case of OxyR and PerR, their effect on virulence is not solely related to the regulation of oxidative stress defense genes. OxyR induces the expression of virulence factors that allow pathogens to evade host innate immunity (74,90), while PerR has been shown to directly regulate an extracellular virulence factor (mitogen factor 3) in Streptococcus pyogenes (117). Other clinically relevant processes, such as biofilm formation (99,119) and the oxidation state-independent regulation of several epigenetically controlled promoters determining phase variation (9,113,114), are also regulated by OxyR.…”
Section: Role Of Oxyr Perr and Ohrr In Virulencementioning
confidence: 99%
“…, 2005). Recently, OxyR has also been shown to regulate secretion of potent cytotoxic factors in P. aeruginosa (Melstrom et al. , 2007).…”
Section: Introductionmentioning
confidence: 99%